Attitudes of Maternal Fetal Medicine specialists on prenatal diagnosis, disability and termination - Aminah Sallam; Marina Gaeta Gazzola; Audrey A. Merriam; Mark Mercurio; Matthew J. Drago (Elsevier, 2023)
Objective: To identify the key attitudes and opinions of Maternal-Fetal Medicine specialists (MFMs) who counsel expectant mothers with a prenatal diagnosis of fetal anomaly surrounding prenatal genetic testing, disability and termination. Methods: We conducted in-depth semi-structured interviews with MFMs across the United States. Participants were recruited through the snowball method beginning with referrals from the MFM on our study team, AM. Interviews were audio-recorded, transcribed, and qualitatively analyzed for themes using modified grounded theory by three reviewers. Results: 2227 codes from 17 interviews were grouped into 18 themes, which were then characterized into six over-arching, topic-oriented clusters: 1) Physician Methodology; 2) Physician Perception of Disability; 3) Physician Experience; 4) Physician-Patient Relationship; 5) Patient Experience; and 6) Termination. Patients' misunderstanding of prenatal genetic screening, diagnostic technology, the implications of certain genetic anomalies, and limited time to explain these factors were identified as major barriers to effective counseling. All MFMs described themselves as informants in the prenatal diagnostic process, and all offered their patients termination following a diagnosis of a severe or lethal congenital anomaly; however, MFMs did not identify a consistent definition of severe or lethal congenital anomaly. MFMs reported fears of being perceived as coercive by patients and a high degree of moral and emotional distress during consultations. Finally, MFMs identified legal, financial and structural barriers that prevented patients from accessing prenatal genetic diagnostic services and termination services. It was felt that these limitations ultimately inhibited autonomous decision making by patients. Conclusions: These findings highlight important barriers faced by MFM providers when trying to provide effective counseling to expectant mothers carrying a prenatal diagnosis of fetal anomaly. Further exploration of these identified barriers may lead to the development of strategies to improve prenatal counseling.